Geochemistry of Late Cretaceous granitoids in the Yidun Terrane: Implications for petrogenesis and tectonic evolution in the eastern Tibetan Plateau. Issue 11 (9th August 2022) - Sun, Zhuanrong; Dong, Guochen; Lemdjou, Yanick Brice; Ketchaya, Yanick Blaise; Pan, Yanning; Guo, Jianheng; Wang, Zhongbao
Abstract : Granites from the eastern Tibetan Plateau record information about the Tethys evolution. This paper reports a systematic study on the N‐S‐trending Late Cretaceous granite belt in the Yidun Terrane. The studied rocks are A‐type granites and I‐type granites with adakitic affinity. From north to south, the studied rocks have intermediate ages and whole‐rock geochemistry that shows a transitional composition. The granites from the northern Yidun Terrane were emplaced at 106–90 Ma. They are characterized by high silica (SiO2 > 70 wt.%) contents, low Mg # (10–38), Eu/Eu*(0.09–0.70), Sr/Y (1–12), and La/Yb (5–21) values and positive to negative ε Hf( t ) (−7.6 to +2.5). In contrasts, granites from the southern Yidun Terrane were emplaced at 87–75 Ma and are intermediate to felsic with SiO2 < 70 wt.%, and higher Mg # (34–69), Eu/Eu* (0.64–1.01), Sr/Y (16–71), La/Yb (22–41) values, and negative ε Hf( t ) values (−9.1 to −1.3). These features together with the Sr–Nd isotopic compositions show that granites from the northern Yidun Terrane were derived from partial melting of ancient crustal from the Yidun Terrane (Xiuwacu granite), with contributions of mantle‐derived components (Queershan and Genie batholiths). Granites from the southern Yidun Terrane likely originated from ancient thickened‐crustal source. The increase of Sr/Y and (La/Yb)N ratios from north to south suggests a crustal thickening, which influenced the magmatic process, resulting in the transition of geochemical composition of the studied granites. An eastward migrating arc post‐collisional model is proposed for the Lhasa‐Qiangtang collision when compared to the eastward younging Late Cretaceous granites in the Qiangtang Terrane. The southward migrating granitic magmatism in the Yidun Terrane was triggered by the eastward migrating rollback of the flat‐subducted Bangong–Nujiang oceanic slab beneath the Qiangtang Terrane. Abstract : The Late Cretaceous granites in the Yidun Terrane (106–75 Ma) are related to the rollback of Bangong–Nujiang oceanic slab. The crustal‐derived granitic magmatism began in the northern Yidun Terrane during 106–90 Ma and gradually migrated to the southern Terrane (87–75 Ma).